Critique of Pesantren Reasoning: Betwen Turāṡ and ʻUrf in Islam Nusantara - Ayatullah Ayatullah; Muhammad Syahrul Hasan; Muhammad Luthfi Ubaidillah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
This article examines the epistemological structure of Pesantren reasoning within the tradition of Islam Nusantara through the dialectical relationship between turāṡ (classical Islamic texts) and ʻurf (local traditions). The study is based on the argument that Pesantren cannot merely be understood as institutions preserving classical Islamic scholarship, but also as dynamic spaces of negotiation between textual authority, socio-cultural realities, and contemporary transformations. The importance of this study lies in the growing challenges faced by Pesantren in responding to modernity, including issues related to industry, economics, science, environment, gender, health, digital technology, and artificial intelligence. This research employs a qualitative approach using library research methods with descriptive-analytical, historical, and philosophical approaches. The study analyzes classical Islamic texts and contemporary scholarly works related to pesantren, Islamic epistemology, and Islam Nusantara through the framework of Muḥammad Ābid al-Jābirī’s epistemology, particularly the concepts of bayānī, burhānī, ‘irfānī, and tajrībī reasoning. The findings demonstrate that pesantren reasoning is not a singular textual system, but a multi-epistemological construct formed through the interaction between textual authority, collective ijtihād, spiritual tradition, and social praxis. Pesantren possess significant strengths in contextualizing turāṡ within social realities, yet also face epistemological limitations due to the dominance of textual reasoning and the limited integration between religious and scientific knowledge. This article contributes to Islamic, social, and cultural studies by positioning pesantren as dynamic epistemological institutions capable of negotiating between tradition and modernity in contemporary Muslim society.